Two yeast plasmids that confer nourseothricin-dihydrogen sulfate and hygromycin B resistance in Neurospora crassa and Cryphonectria parasitica. - Robert Phillip Smith; Myron L Smith (Fungal Genetics Reports, 2007)
Two plasmids that were previously used with yeast, pRS41N and pRS41H, were found to confer clonNAT and hygromycin B resistance, respectively, in the filamentous fungi Neurospora crassa and Cryphonectria parasitica. These plasmids are suitable for routine cloning and for use in forcing heterokaryons and are available through the FGSC.